1989
DOI: 10.1039/an9891401413
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of aryl oxalates as peroxyoxalate chemiluminescence reagents

Abstract: Eight aryl oxalates having an alkyoxy moiety were synthesised to improve the solubility in acetonitrile for the peroxyoxa I ate chem i I u m i nescence reaction system. Of these, bis [ 2-(3,6-d ioxa heptyloxyca rbo nyl)-4-fluorophenyl] oxalate showed the highest solubility (1685 mM). To evaluate these esters together with some known aryl oxalates as chemiluminescence reagents, a simple and rapid method using a flow injection system was developed. The chemiluminescence reaction system consisted of an oxalate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Tests have shown that alternative oxalates may be more suitable in special cases. [55][56][57] The chemiluminescent reaction of peroxyoxalate with TCPO has been studied in the presence of various catalysts, consisting of substituted imidazoles. 15 Some metal cations [particularly Cu(II)], enhance the chemiluminescence intensity produced by peroxyoxalates.…”
Section: Oxalate Estersmentioning
confidence: 99%
“…Tests have shown that alternative oxalates may be more suitable in special cases. [55][56][57] The chemiluminescent reaction of peroxyoxalate with TCPO has been studied in the presence of various catalysts, consisting of substituted imidazoles. 15 Some metal cations [particularly Cu(II)], enhance the chemiluminescence intensity produced by peroxyoxalates.…”
Section: Oxalate Estersmentioning
confidence: 99%
“…ROS is an important indicator and a major characteristic of several pathological conditions, including cancer, where elevated intracellular levels have been reported in disease conditions . ROS‐responsive drug delivery carriers currently being developed mostly involve organochalcogens (selenium, tellurium, diselenium, and ditellurium), organoboron compounds (aryl boronic ester), sulfur containing compounds (thioether, thioketal, vinyl dithioether), aryl oxalates, and ferrocenes, either as cross‐linkers or as important constituents of polymeric backbone. Although very few studies have been reported for ROS‐responsive nanogels, it would be worthwhile to review some of the important reported results, due to the potential applicability of the ROS‐responsive units in the development of advanced redox‐responsive nanogel‐based systems in the near future.…”
Section: Emerging Areas In the Field Of Redox‐responsive Materialsmentioning
confidence: 99%
“…On the basis of earlier work, there would appear to be at least two characteristics that are of significance in the design of useful reagent molecules for peroxyoxalate chemiluminescence. [4][5][6][7][9][10][11] The first criterion is that the substituents surrounding the central oxalate moiety must exhibit a significant degree of electron-withdrawing character. This results in an acyl carbon that is sufficiently activated towards nucleophilic attack by the hydroperoxide anion, which in the presence of further base leads to the generation of reactive intermediates which transfer the excitation energy to a fluorophore compound [12][13][14] (see Scheme 1).…”
Section: Abstract: Aqueous Peroxyoxalate Chemiluminescene; Oxamide Re...mentioning
confidence: 99%